Charge-Shift Bonding in Xenon Hydrides: An NBO/NRT Investigation on HXeY···HX (Y = Cl, Br, I; X = OH, Cl, Br, I, CCH, CN) via H-Xe Blue-Shift Phenomena - Zhang, Guiqiu; Su, Yue; Zou, Xiaoran; Fu, Lei; Song, Junjie; Chen, Dezhan; Sun, Chuanzhi (Frontiers in Chemistry, 2020)
Noble-gas bonding represents curiosity. Some xenon hydrides HXeY (Y = Cl, Br, I) and their hydrogen-bonded complexes HXeY···HX (Y = Cl, Br, I; X = OH, Cl, Br, I, CN, CCH) have been identified in matrixes by observing H-Xe frequencies or its monomer-to-complex blue shifts. However, the H-Xe bonding in HXeY is not yet completely understood. Previous theoretical studies provide two answers. The first one holds that it is a classical covalent bond, based on single ionic structure H-Xe+ Y-. The second one holds that it is resonance bonding between H-Xe+ Y- and H- Xe+-Y. This study investigates the H-Xe bonding, via unusual blue-shifted phenomena, combining with some NBO/NRT calculations for chosen hydrogen-bonded complexes HXeY···HX (Y = Cl, Br, I; X = OH, Cl, Br, I, CN, CCH). This study provides new insights into the H-Xe bonding in HXeY. The H-Xe bond in HXeY is not a classical covalent bond. It is a charge-shift(CS) bond, a new class of electron-pair bonds, which is proposed by Shaik and Hiberty et al. The unusual blue shift in studied hydrogen-bonded complexes is its H-Xe CS bonding character in IR spectroscopy. It is expected that these studies on the H-Xe bonding and its IR spectroscopic property might assist the chemical community in accepting this new-class electron-pair bond concept.